The September house - Orlando, Carissa (Berkley, 2023)
"A thrilling psychological horror debut about a woman who is determined to stay in her dream home even after it becomes haunted, no matter the cost ... You can survive anything. That's what Margaret tells herself when the walls of her house start to drip blood every September. She's learned how to live with it ... and the other terrifying apparitions that have made the sprawling Victorian house she and her husband bought four years ago turn from a dream home into a living nightmare. But she can outlast all of it. Hal felt differently, though. Her husband couldn't take the hauntings anymore, and he left. But now he's not returning calls, and their daughter Katherine arrives, intent on looking for her missing father, convinced something grim has happened to him. With every desperate attempt Katherine makes at finding Hal, the hauntings at the September House grow more harrowing, because there are some secrets the house needs to keep" --